2000
DOI: 10.1130/0091-7613(2000)028<0059:domtd>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Minoan tsunami deposits

Abstract: The Hellenic arc is a terrane of extensive Quaternary volcanism. One of the main centers of explosive eruptions is located on Thera (Santorini), and the eruption of the Thera volcano in late Minoan time (1600-1300 B.C.) is considered to have been the most significant Aegean explosive volcanism during the late Holocene. The last eruptive phase of Thera resulted in an enormous submarine caldera, which is believed to have produced tsunamis on a large scale. Evidence suggesting seawater inundation was found previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
62
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(65 citation statements)
references
References 17 publications
(21 reference statements)
2
62
0
1
Order By: Relevance
“…Several years ago an effort was made to study systematically the history of the Eastern Mediterranean Sea tsunami (Papadopoulos and Chalkis 1984;Koutitas and Papadopoulos 1998;Minoura et al 2000, Papadopoulos andPapadopoulos et al , 2005Perissoratis and Papadopoulos 1999;Papadopoulos 2001Papadopoulos , 2003Papadopoulos and Plessa 2001). In this paper, we compile a new tsunami catalogue for Cyprus and the Levantine Sea that extends from antiquity up to the present.…”
Section: Introductionmentioning
confidence: 96%
“…Several years ago an effort was made to study systematically the history of the Eastern Mediterranean Sea tsunami (Papadopoulos and Chalkis 1984;Koutitas and Papadopoulos 1998;Minoura et al 2000, Papadopoulos andPapadopoulos et al , 2005Perissoratis and Papadopoulos 1999;Papadopoulos 2001Papadopoulos , 2003Papadopoulos and Plessa 2001). In this paper, we compile a new tsunami catalogue for Cyprus and the Levantine Sea that extends from antiquity up to the present.…”
Section: Introductionmentioning
confidence: 96%
“…Dominey-Howes (2004), however, suggested that there were no terrestrial geological evidence identified indicating a LBA eruption generated an east Mediterranean-wide tsunami. So the volcanic eruption could not be responsible for the tsunami, as well as the tsunami deposits mentioned by Minoura et al (2000). These results may imply (1) some local tsunamis occurred prior to the eruption instead of tsunamigenesis and tephra production was simultaneous or (2) a far-field tsunami occurred related to caldera collapse.…”
mentioning
confidence: 48%
“…Minoura et al (2000) were able to identify significant stratified findings (ca. 10 cm thick sandy layer) which may represent the Late Bronze Age tsunami deposits in a small town Didim on the Aegean coast of western Turkey and also in Fethiye, 20 km east of Dalaman.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Observation of storm surges on the coasts of the Aegean Sea suggests that they are generally agents of erosion and do not produce regionally extensive deposits on land areas (Minoura et al, 2000). Mixed inclusion of buoyant materials in the unsorted silty sand layer supports the interpretation of the abrupt landward transport of materials by turbidity currents.…”
Section: Discussionmentioning
confidence: 96%